Seed Transmission of Three Viruses in Two Pear Rootstock Species Pyrus betulifolia and P. calleryana - Liu Li; Lihong Wen; Guoping Wang; Yuzhuo LYU; Zuokun Yang; Xiaoping Yang; Qingyu Li; Ni Hong (Viruses, 2022)
Viral seed transmission causes the spread of many plant viral diseases. Pyrusbetulifolia and P. calleryana are important rootstock germplasms for pear production in China. This study revealed the widespread infection of apple stem grooving virus (ASGV), apple chlorotic leaf spot virus (ACLSV), and apple stem pitting virus (ASPV) in maternal trees of P. betulifolia and P. calleryana by nested multiplex reverse transcription-polymerase chain reaction (nmRT-PCR) assays. Seeds from eight P. betulifolia and two P. calleryana trees had positive rates of 15.9–73.9%, 0–21.2%, and 40.4% for ASGV, ASPV, and ACLSV, respectively. At the cotyledon and 6–8 true leaf stages, seedlings grown from seeds of infected trees gave positive rates of 5.4% and 9.3% for ASGV, 6.7% and 15.6% for ACLSV, and 0% and 2.7% for ASPV, respectively. Incidence in nursery P. betulifolia seedlings of 10.1%, 5.3%, and 3.5% were determined for ASGV, ACLSV, and ASPV, respectively. The nucleotide sequences of coat protein (CP) and movement protein coding genes of both ASGV and ASPV, and CP gene of ACLSV from maternal trees, seeds, and seedlings were analyzed. Sequence identities and phylogenetic comparison with corresponding sequences from GenBank demonstrated that molecular variation occurred within ASGV, ACLSV, and ASPV isolates, with most sequences determined here had close relationships with reported isolates infecting pear or formed independent clades. This is the first report on the seed transmission and the molecular characteristics of these viruses infecting two rootstock species. These findings provided important evidence in management effort for pear viral diseases.